Penerapan Kode Etik Foto Jurnalistik Pada Berita Hukum Dan Kriminal Di Media Online Sumeks.co - Juan Muliawan Fatrin (Tabayyun: Journal of Journalism, 2023)
This thesis is entitled "Application of the Photojournalistic Code of Ethics in Legal and Criminal News in Sumeks.co Online Media". The problem raised from this research is how to apply the photojournalistic code of ethics to legal and criminal news in online media Sumeks.co, how to photo news portals on Facebook, Twitter, Instagram online media Sumeks.co. This type of research is qualitative, the main or primary source is the acquisition of information in the form of words and sentences, either in the form of questions or statements. Data collection techniques through observation and documentation and use semiotic theory. Snowball sampling was used and the writer was able to gather more information to fill in the data gaps. Based on these findings, it is clear that most of the views of journalists about how the Journalistic Code of Ethics should be applied are contrary to the regulations stipulated therein. Likewise, the Journalistic Code of Ethics regulates the behavior of journalists and the media regarding the use of photographs in reporting. As with other online media, Sumeks.co will strive to comply with the Photojournalism Code of Ethics in all its reporting. However, this is easier said than done, given the nature of the Code of Conduct itself and the difficulty of coordination between journalists in the field and news editors. In addition, also see how the Sumeks.co media portal photos on other social media such as Instagram, Facebook, and Twitter